An internet marketing adoption framework for small business enterprises - Mokhtar, Noor Fadhiha; Burgess, Stephen (2010)
Small business enterprises are the backbone of economic growth and innovation. The existence of the Internet provides opportunities for these enterprises to gain the benefits of Information and Communication Technologies in their business operations. However, small business enterprises often face a variety of challenges such as limited financial resources, a shortage of skilled workers, and inadequate infrastructure (such as communication connectivity or electricity supply particularly in rural areas) in adopting new technology in their business operations. Many small business enterprises are not engaged with appropriate business strategies which lead to informal and mixed marketing approaches in their businesses. This paper proposes an Internet marketing adoption framework for small business enterprises. The proposed framework of Internet marketing would be incorporated as part of the business strategies for small business enterprises in order to assist owners and managers (who are often poor planners). This paper presents a review of the main indicators in the proposed framework, which are e-readiness, aims and strategies (which will lead to the Internet marketing approach by small business enterprises), the Internet marketing approach and the evaluation of the Internet marketing performance. The 4C’s (customer, communication, convenience, and cost) (Smith, 2003) are the factors that will be considered while implementing the Internet marketing approach for small business enterprises. These 4C’s are the ‘online’ extension of basic marketing principles. The Internet marketing performance will be evaluated to indicate whether the Internet marketing approach contributes to the success of the businesses or vice-versa.